Literasi Green Economy dan Animasi Pilah Sampah untuk Edukasi Lingkungan di SMA Muhammadiyah 3 Tulangan - Diah Krisnaningsih; Ninda Ardiani; Masruchin Masruchin (BADAN PENERBIT STIEPARI PRESS, 2025)
The environmental crisis is becoming an increasingly pressing issue as development increases without adequate attention to ecological aspects. Negative impacts such as air, soil, and water pollution, as well as extreme climate change, demonstrate that development is not aligned with the principles of environmental sustainability. One serious problem is the increasing volume of waste, from households, schools, and industry. Unfortunately, public awareness of waste sorting and management remains relatively low. Poorly managed waste can cause pollution and long-term health threats. Separating organic and inorganic waste is a crucial step in creating an effective and environmentally friendly waste management system. Therefore, environmental education is a strategic effort to foster awareness from an early age, particularly in the school environment. Through an educational approach and engaging delivery, it is hoped that students will more easily understand the importance of maintaining a clean and sustainable environment. This community service activity aims to improve Green Economy literacy and waste sorting education for students at Muhammadiyah 3 High School, Tulangan, Sidoarjo. The primary target group is 12th-grade students from five classes who are directly involved in the outreach activities. The method used is the screening of interactive and educational motion graphic animation media, making it easier for students to understand the material. This media was chosen because it is visual, engaging, and in line with the characteristics of a young generation familiar with technology. As a form of concrete support, the team also provided green (organic) and yellow (inorganic) trash cans throughout the school environment. It is hoped that this activity will not only broaden students' understanding of the importance of waste sorting but also foster positive, sustainable habits. Furthermore, this activity is the first step in developing a young generation with social responsibility and environmental awareness.